2012
DOI: 10.1517/17425255.2012.668528
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic reactions and metabolism of sulfur-containing drugs

Abstract: Incomplete understanding of mechanisms culminating in IDR occurrence represents a monumental impediment toward their abrogation. Moreover, current technology utilized to predict their manifestation (including structure-toxicity relationships) is not infallible and thus, development of novel tools and strategies is indispensible. In an attempt to streamline clinical development and drug approval processes, consortiums have been instated under the US FDA Critical Path Initiative. Collectively, these parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…A potential limitation of compound A is that its reaction with glutathione may indicate a lack of specificity. Many drugs that target sulfhydryl groups are in fact nonspecific and may react with reactive cysteines on other proteins (Zuniga et al, 2012). There are, however, many examples of sulfhydryltargeting drugs in current use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential limitation of compound A is that its reaction with glutathione may indicate a lack of specificity. Many drugs that target sulfhydryl groups are in fact nonspecific and may react with reactive cysteines on other proteins (Zuniga et al, 2012). There are, however, many examples of sulfhydryltargeting drugs in current use.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their reversibility after DTT treatment, these new compounds likely activate LCAT by forming a mixed disulfide with LCAT by S-methylating Cys31. Again, a limitation of this new class of compounds is that many drugs that target sulfhydryl groups are nonspecific and may react with reactive cysteines on other proteins (Zuniga et al, 2012). Previous studies of the N-methylthio class of lactams have shown that the N-S bond is relatively resistant to cleavage by most types of nucleophiles but is susceptible to thiophiles (Woulfe et al, 1985;Shah and Cama, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Sulfur atom has been thought to be the site of bioactivation of these organosulfur compounds resulting in conceivably toxic metabolites. 39 Biological oxidations of small molecules such as N-acetylthiourea, N-methylthiourea show that sulfur is a soft nucleophile, and is easily oxidized by oxidants such as iodine, HOBr and HOCl, which are found in the physiological environment albeit in low concentrations. 40 The difference in oxidative environment and oxidizing species has a large bearing on the intermediates and subsequent products.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 lists some important characteristics of the microarray platforms analyzed in this work. These characteristics can affect microarray performance [7-10]. The length of probes represents a tradeoff between sensitivity and specificity, with longer probes being generally more sensitive and shorter being more specific.…”
Section: Introductionmentioning
confidence: 99%